Platelet-rich plasma combined with lyophilizing thrombin powder for the treatment of complicated enterocutaneous fistula: a case report - He, Chao; Liu, Kui; Zhao, Zhijie; Lai, Zhihao; Qu, Linlin (Frontiers in Surgery, 2023)
Background Enterocutaneous fistula is one of the most challenging problems facing surgeons. In severe cases, a large amount of fluid loss can lead to problems such as water and electrolyte acid-base imbalance, malnutrition, infection, and organ dysfunction. Here we reported a case of platelet-rich plasma combined with lyophilizing thrombin powder for the treatment of complicated enterocutaneous fistula. Case presentation A 48-year-old male, more than 2 years after the operation of abdominal trauma, the leakage of the fistula in the right upper abdominal wall was accompanied by fever for 3 days. The Contrast Fistulography and upper abdomen CT accurately depicted the entry of the meglumine diatrizoate into the small intestine through the small fistula. The patient had a large abdominal wall defect and severe intestinal adhesions. Reoperation may lead to more serious ECF. Therefore, we decided to seal the fistulas with PRP combined with lyophilizing thrombin powder. Conclusions The findings in this case report suggest that the combination of PRP and lyophilized thrombin powder holds promise as a viable approach for managing ECF in patients with chronic abdominal wall fistulas, as it appears to facilitate fistula closure, reduce healing time, and improve patient outcomes